A Swallow Does Not Make a Summer. Towards a Theory of the Human Aesthetic as a Habitual Disposition - Portera, Mariagrazia (Aisthesis, 2024)
This paper is part of a broader effort to reinterpret the human aesthetic through the lens of the notion of habitus or disposition, considering the recent resurgence of interest, within the field of contemporary aesthetics, in Aristotelian virtues (“aesthetic virtue”) and, within the field of analytic metaphysics, in the concept of power. Assuming that virtues in aesthetics are excellences of the character that enable us to cor-respond appropriately to (active) aesthetic objects, this paper explores how and to what extent an (aesthetic) subject can achieve self-knowledge of having reached that “level of excellence” of their (aesthetic) disposition or power. Additionally, it suggests that experiences of failure might have a role, ex negativo, in this process. The text is organized into paragraphs, each addressing one of the following points: 1. what a disposition (or habitus or capacity or power) is; 2. dispositions in ethics (Aristotelian virtues); 3. why and to what extent the human aesthetic can be understood as a disposition or power, referencing some recent literature on the notion of “aesthetic virtue”; 4. the relationship between aesthetic dispositions and the experience of (aesthetic) failure.